CDW Integrated Management, from Linear to Circular Economy in Bogota (2019)
Construction and demolition waste (CDW) has become an environmental, social and economic problem in some regions. Many initiatives to increase CDW recycling and concrete with recycled aggregates have failed or have not accomplished the goals, due to the lack of good management. In Bogotá, even though regulations establish that 25% must be harnessed, only 17% is achieved. To obtain rates as high as the global ones, a CDW diagnosis in works is run and policy instruments that would allow the application of a circular economy concept as opposed to a linear economy are determined. It is found that economic and informative instruments are the most popular worldwide and the most requested at the national level, in comparison to regulatory instruments which currently prevail in Bogotá. Likewise, the literature highlights prevention actions and the national context prefers recycling and disposition actions.